SDN enabled space-terrestrial integrated network architecture of railway system - Yinglei TENG; Xin LI; Jian WANG; Bogen CAI; Mei SONG (物联网学报)
In view of the current situation that it is difficult to guarantee the safe and reliable transmission of data with the poor geographical environment in the single standard train communication network,the communication needs of each business of the railway system were investigated and a space-terrestrial integrated network architecture based on software defined network (SDN) and network functions virtualization (NFV) was proposed.By focusing on the controller to manage the physical facilities,the architecture realized decoupling application and physical infrastructure.The design of the architectural details and the requirements of the agreement for the architecture in the functional requirements and the information flow were discussed.In the end,the performance comparison between the space-terrestrial integrated network and other single-system network coverage was given,problems remaining to be solved and some feasible solutions faced by the space-terrestrial integrated network were briefly discussed.